Seasonal Prevalence and Determinants of Gastrointestinal Parasitism in Goats of Indore District: A Comprehensive Epidemiological Study - Solanki, Himanshi; Agrawal, Vivek; Shakya, Mukesh; Kashiram Jayraw, Anantrao; P. Jatav, Gaya; Jamra, Nirmala (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Gastrointestinal (GI) parasitism is a major challenge affecting goat health and productivity, particularly in developing regions where goats are vital for the livelihoods of marginal farmers and landless laborers. This study investigated the prevalence and associated determinants of GI parasitism in goats from four blocks of Indore district, Madhya Pradesh, during the summer and monsoon seasons of 2024. A total of 312 fecal samples were analyzed using flotation, sedimentation, and the McMaster method, while coproculture was employed to recover infective larvae. Statistical analysis revealed significant associations between GI parasitism and factors such as season, age, sex, breed, rearing system, body condition, and farmer practices. The findings underscore the importance of targeted control strategies and farmer education to mitigate the burden of GI parasitism in goats.